Countess Kate - Yonge, Charlotte M. (Charlotte Mary), 1823-1901 (Salt Lake City, UT : Project Gutenberg, 2002)
"Countess Kate" by Charlotte M. Yonge is a novel likely written in the early 20th century. The story follows the charming and mischievous young Katharine Umfraville, who unexpectedly inherits the title of Countess of Caergwent upon the death of a distant relative. As she navigates her new status and the responsibilities it entails, she faces the challenge of adapting to the expectations of her aristocratic aunts while longing for the carefree life she led with her adoptive family. The opening of "Countess Kate" introduces us to the joyful chaos of Kate's life before her dramatic transition into the nobility. We meet her lively and imaginative character as she interacts with her cousin Sylvia and reflects on her daydreams of wealth and grandeur. However, the tone quickly shifts upon the revelation of her inheritance, which brings a mix of excitement and trepidation. As Kate prepares for her new life in London with her aunts, the narrative highlights her innocence, creativity, and the anxiety that comes from leaving behind the only family she has known. The stage is set for a tale of growth and self-discovery, where Kate must learn to balance her spirited nature with the expectations of her new role. (This is an automatically generated summary.)
Release date is 2002-06-01
Transcribed from the 1902 Macmillan and Co. (3z(BCountess Kate and The Stokesley Secret(3y (Bedition by David Prices
Keywords: Orphans -- Juvenile fiction; Children -- Conduct of life -- Juvenile fiction; London (England) -- Juvenile fiction; Inheritance and succession -- Juvenile fiction